Developing urban space: the changing role of NGOs in Bangladesh. Issue 2 (17th February 2017) - Chowdhury, Mushtaque Raza; Jahan, Ferdous; Rahman, Rehnuma
ABSTRACT: Rapid urbanisation has been an emerging issue in recent decades, particularly for developing countries such as Bangladesh. As one of world's largest international NGOs, BRAC, based in Bangladesh, is transiting towards a more integrated approach for alleviating urban poverty. This article presents BRAC's current journey for eradicating urban poverty and outlines the characteristics of urban poverty, key issues faced by the urban poor, and learning that BRAC has accumulated through its urban interventions. Introducing the concept of "coproduction", the article identifies BRAC's priorities to eradicate urban poverty within the context of an overall urban strategy.